Antioxidant and antiinflammatory of clove extract (Syzigium aromaticum) in skeletal muscle damage - Ningrum, Tyas Sari Ratna; Wardhani, Riska Risty; Sugihartini, Nining (Pharmaciana, 2025)
Clove extract is a natural ingredient abundant in Indonesia that has various benefits, including being an antioxidant and anti-inflammatory. Although Research has been conducted, it has been limited to discussing the effects of clove extract on muscle damage. This study aims to determine the effect of clove extract on skeletal muscle damage due to excessive eccentric exercise in mice. We used experimental research methods by a post-test only with control group design. Fifteen male mice were randomized into 5 groups. Group I: Normal control, Group II: Negative control, treatment group with a dose of 100 mg/kg BW, treatment group with a dose of 150 mg/kg BW, and treatment group with a dose of 250 mg/kg BW. Measurement of Nicotinamide Adenine Dinucleotide Phosphate Oxidase (NOX) and Toll Like Receptor4 (TLR 4) levels were carried out using the ELISA method via Quadriceps muscle samples, and skeletal muscle damage was viewed through an x1000 light microscope. The results of this study carried out using ANOVA showed results of p 0.004 and 0.006, which means that there was a decrease in oxidative stress as measured using NOX and a decrease in the inflammatory stimulator TLR 4 in skeletal muscle damage due to eccentric exercise.ANOVA test results show that there are differences in influence between treatment groups and show that clove extract has benefits as an antioxidant and anti-inflammatory in muscle damage. According to this study, clove extract has the potential to be an antioxidant and anti-inflammatory which can reduce NOX levels and reduce the inflammatory, mediator TLR4 in muscle damage caused by excessive eccentric exercise.